Crise hipercalcémia secundária a hiperparatiroidismo primário durante a gravidez - Branco, MR (2012)
Primary hyperparathyroidism is a rare occurrence in pregnancy with significant risks to the mother and the foetus, witch is related to the level of serum calcium. A 41-year-old women, gravida 2, para 1, presented at 22 weeks gestation with nausea, vomiting and mild cognitive dysfunction associated with hypercalcemic crisis. The hypercalcemia was observed to be related to parathyroid hyperplasia that was surgically removed. Complete resolution of her symptomatology and hypercalcemia occurred postoperatively. The pregnancy was complicated with transient hypertension. A small for gestational age healthy male infant was delivered at term with no neonatal complications related with this pathology.